The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1634/theoncologist.2013-0243
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Breast Cancer Treatment and Outcomes: Biological, Social, and Health System Determinants and Opportunities for Research

Abstract: Racial disparities in breast cancer mortality have been widely documented for several decades and persist despite advances in receipt of mammography across racial groups. This persistence leads to questions about the roles of biological, social, and health system determinants of poor outcomes. Cancer outcomes are a function not only of innate biological factors but also of modifiable characteristics of individual behavior and decision making as well as characteristics of patient-health system interaction and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
196
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(200 citation statements)
references
References 97 publications
3
196
1
Order By: Relevance
“…While many providers are aware of mortality disparities in breast cancer that can be linked to these subtypes, future efforts to educate HCPs should build upon this awareness by presenting new research that links these disparities to incidence of specific breast cancer subtypes. 31,32 Recent data suggests that beyond querying patients about family history of breast cancer, asking patients about the pathologic characteristics of their family member's breast cancer can help improve genetic risk assessment. 33 Efforts to provide information to HCPs are important in disseminating prevention strategies for BBC.…”
Section: Discussionmentioning
confidence: 99%
“…While many providers are aware of mortality disparities in breast cancer that can be linked to these subtypes, future efforts to educate HCPs should build upon this awareness by presenting new research that links these disparities to incidence of specific breast cancer subtypes. 31,32 Recent data suggests that beyond querying patients about family history of breast cancer, asking patients about the pathologic characteristics of their family member's breast cancer can help improve genetic risk assessment. 33 Efforts to provide information to HCPs are important in disseminating prevention strategies for BBC.…”
Section: Discussionmentioning
confidence: 99%
“…Often, cultural, social, economic, and biological factors interplay together in shaping the risk of breast cancer (Wheeler et al 2013). Studies have suggested that the effect of racial disparities is not comparable to the effect of socioeconomic disparities in explaining the risk of breast cancer (Baquet and Commiskey 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The U.S. Department of Health and Human Services made it clear that elimination of health disparities was a national priority [7]. If cancer patients receive less-than-standard treatment, differences in outcomes are likely to result [8]. Reducing these disparities is a critical next step for China.…”
Section: Introductionmentioning
confidence: 99%